Analisis Pendidikan Kewarganegaraan dalam Meningkatkan Civic Engagement - Ahmad Muhammad Mustain Nashoha; Ashfiyah Nur Atqiya; Agreiccia Amelia Fitrianti; Laili Latifah; Adhi Fajar Hermawan; Ali Bachtiar Galih P (Jurnal Hukum dan Sosial Politik, 2025)
Civic education plays a central role in shaping responsible and politically aware citizens. Amid the challenges of globalization, it serves as a strategic tool to enhance civic engagement. This article aims to examine the contribution of civic education in promoting civic engagement in Indonesia. Using a qualitative approach through literature review, this study analyzes various research findings and theoretical frameworks related to the relationship between civic education and socio-political participation. The findings indicate that effective civic education can develop civic competencies, including knowledge, critical thinking skills, and positive civic dispositions. These competencies significantly influence citizens' awareness and active participation in democratic life. Contextual and progressive strategies and curricula are needed to ensure civic education can adapt to social dynamics and serve as a platform for shaping democratic and inclusive citizen character.